Effect of thawing temperature on motion characteristics of frozen-thawed ram spermatozoa - BAG, SADHAN; JOSHI, ANIL; MATHUR, A K; RAWAT, P S; MITTAL, J P (The Indian Journal of Animal Sciences, 2012)
Semen of adult Malpura rams was processed for freezing after initial dilution @ 1000 million spermatozoa/ml. Extended semen samples were aspirated into 0.5 ml straws and frozen in a programmable cell freezer. Straws were thawed at 50°C or 60°C for 10 sec and the motion characteristic of spermatozoa were assessed by computer-assisted sperm analysis technique. The mean post·thaw recovery of motile spermatozoa at 60°C thawing was significantly higher (P